LAS EXPRESIONES DEL PODER EN EL VOCABULARIO DE MARSILIO DE PADUA (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
The paper startes from the emphasis bestowed by Marsilius of Padua on an accurate definition of the basic terms used in political philosophy. Because, according to him, most of political problems caused by the Papacy stems from the false interpretation of these terms, in which Pope attempt to justify an unsuitable temporal power maintaining even the supreme power or plenitudo potestatis. Therefore the philological analysis of the main terms, used by medieval thought to express the relationships of power, leads to place aright the human authority and refuse any political power for the Pope or priests in this world.